MAXMUD QASHQARIYDIŃ «DEVONU LUǴAT AT-TÚRK» SÓZLIGINDE KELGEN BAZÍ GLYUTTONIMLERDIŃ QARAQALPAQ TILINE QATNASÍ HÁM LINGVOKULTUROLOGIYASÍ - Nurlıbekova, G.M. (ILIM hám JÁMIYET, 2024)
In this article, some glutonyms found in the lexical layer of the Karakalpak language are studied together with glutonyms found in the dictionary of Devanu at-Turk, which is considered the most valuable work of its time today. The meaning of the mentioned words in the 11th century and their meaning today will be revealed; the linguocultural study of gastronomic terms is seen as a way of discovering many cultures left behind in history.